What the jaguar told her - Méndez, Alexandra V. (Levine Querido, 2022)
Jade feels totally out of place when she is forced to move to Atlanta, and she wishes she could go back to her home in Chicago, where her friends and Abuela are. The only good thing about the move is her walk to school along a trail that runs through the woods behind her house. There, she meets Itztli, an elderly storyteller who exists between dreams and reality, and she is fascinated by his ancestral stories from Mexico. But when her Abuela has a stroke, the Twin Towers are attacked in New York City, and Jade starts becoming someone or something she doesn't understand, Itztli's stories begin to connect more to Jade's own life.